GENPI’S STRATEGY IN THE DEVELOPMENT DIGITAL TOURISM DESTINATION IN LAMPUNG PROVINCE - Dian Kagungan; anna gustina zainal; Feni Rosalia (Universitas Padjadjaran, 2021)
Provincial tourism development Lampung is the leading tourist destination in Indonesia the locomotive of development and provide increased welfare on Public. This research aims to determine GenPi’s strategy in developing a policy digital tourism destination towards Lampung go digital. The method in this research is qualitative, the location of this research is Tahura Market, Teluk Pandan District, Pesawaran Regency, Lampung Province. Data were collected through interviews and FGDs, The informants in this study were the administrators of GenPi Lampung, two administrators of Tahura Market, and two visitors to Tahura Market tours. Based on the research results GenPi’s startegy, it is known to encouraging the development of tourism in Lampung, GenPI Lampung plays an important role in developing tourism in Lampung by carrying out vigorous promotions on social media, one of which is by sending content on tourist destinations in Lampung to thep latform GenPi.co. GenPI Lampung also carries out activities offline, one of which is by creating a digital tourism destination in the form of a market. Digital tourism destination is the result of demands of era the digital considering the dominated today’s travelers generation, millennials tend to like the visit to destinations that provide new and fun experience. The concept of digital tourism destination refers to a destination that is creative, has photogenic spots to upload on social media, and goes viral on social media.